2010 IEEE 51st Annual Symposium on Foundations of Computer Science 2010
DOI: 10.1109/focs.2010.53
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Framework for Testing Linear-Invariant Properties

Abstract: In the history of property testing, a particularly important role has been played by linearinvariant properties, i.e., properties of Boolean functions on the hypercube which are closed under linear transformations of the domain. Examples of such properties include linearity, Reed-Muller codes, and Fourier sparsity. In this work, we describe a framework that can lead to a unified analysis of the testability of all linear-invariant properties, drawing on techniques from additive combinatorics and from graph theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 64 publications
1
74
0
Order By: Relevance
“…Bhattacharyya, Grigorescu and Shapira [15] have shown that non-monotone matroid-freeness properties are testable when the matroid is restricted to be of complexity 1. Interestingly, their proof uses arithmetic regularity lemmas, like Green [21] and us, instead of reductions to hypergraph properties as in [28,27,32].…”
Section: Significance Of Problems/resultsmentioning
confidence: 99%
“…Bhattacharyya, Grigorescu and Shapira [15] have shown that non-monotone matroid-freeness properties are testable when the matroid is restricted to be of complexity 1. Interestingly, their proof uses arithmetic regularity lemmas, like Green [21] and us, instead of reductions to hypergraph properties as in [28,27,32].…”
Section: Significance Of Problems/resultsmentioning
confidence: 99%
“…However, a general result analogous to Theorem 4.5 remains elusive. For that, as Bhattacharyya, Grigorescu and Shapira [BGS10] show, the following question needs to be resolved.…”
Section: That Given Input Function F : F N → [R] Decides Only Basedmentioning
confidence: 99%
“…Finally, about one-sided testable properties, the analog of Theorem 4.3 is also known. If a property P is obliviously one-sided testable, then it is "semi-subspace-hereditary" [BGS10]. For details, consult the paper, but roughly speaking, a semi-subspace-hereditary property P is close to a subspace-hereditary property P , in the sense that P contains P and any function f : F n → [R] that's ε-far from P is not in P (for large enough n in terms of ε).…”
Section: Theorem 47 ([Bfh + 13]) Any Subspace-hereditary Affine-inmentioning
confidence: 99%
See 2 more Smart Citations